Ice discharge error estimates using different cross-sectional area approaches: a case study for the Canadian High Arctic, 2016/17 - Sánchez-Gámez, Pablo; Navarro Valero, Francisco José (Journal of Glaciology, 2018)
We analyse the various error sources in the estimation of ice discharge through flux gates, distinguishing the cases with ice-thickness data available for glacier cross-sections or only along the centreline. For the latter, we analyse the performance of three U-shaped cross-sectional approaches. We apply this methodology to glaciers of the Canadian High Arctic. The velocity field is the main error source for small and medium-size glaciers (discharge 100 Mt a−1 ) with high velocities (>100 m a−1 ) the error in crosssectional area dominates. Thinning/thickening between ice-thickness and velocity measurements should be considered, as it implies systematic errors up to 8% in our study. The U-shaped parabolic approach, which allows for an adjusted estimation when the ice-thickness measurement point is displaced from the glacier centreline, performs best, with small bias and admissible standard error. We observe an increase of ice discharge from the main glaciers (Trinity and Wykeham) of the Prince of Wales Icefield from 2015 to 2016, by 5 and 20%, respectively, followed by a decrease in 2017, by 10 and 15%, respectively. Belcher Glacier, of the Devon Ice Cap, maintains similar discharges during 2015–17.